Estimation of aortic pulse wave velocity based on waveform decomposition of central aortic pressure waveform. (29th October 2021) - Liu, Wenyan; Yao, Yang; Yang, Jinzhong; Song, Daiyuan; Zhang, Yuelan; Sun, Guozhe; Xu, Lisheng; Avolio, Alberto
Abstract: Objective. Aortic stiffness is associated with risk of cardiovascular events. Carotid-femoral pulse wave velocity (cfPWV) is the current noninvasive gold standard for assessing aortic stiffness. However, the cfPWV measurement is challenging, requiring simultaneous signals at the carotid and femoral sites. Approach. In this study, the aortic PWV is estimated using a single radial pressure waveform and compared with cfPWV. 111 subjects' aortic PWVs are estimated from the decomposition of the derived central aortic pressure waveform based on three types of reconstructed flow waveform: the peak of triangular flow waveform based on 30% ejection time ( Q 30%tri ), the peak of triangular flow waveform based on inflection point ( Q tri ), and averaged flow waveform ( Q avg ). The central aortic pressure waveform is derived from a radial pressure waveform via a validated transfer function. Main results. The Q avg is used for estimating aortic PWV without the determination of the peak point of the triangular flow waveforms. The estimated aortic PWV shows good agreement with cfPWV. The mean difference ± SD is 0.29 ± 1.50 m s −1 ( r 2  = 0.29, p < 0.001) for the Q 30%tri ; 0.27 ± 1.40 m s −1 ( r 2  = 0.38, p  < 0.001) for the Q tri ; 0.23 ± 1.39 m s −1 ( r 2  = 0.40, p  < 0.001) for the Q avg . The correlation between estimated aortic PWV based on Q 30%tri and measured cfPWV is weak. The results of Q tri and Q avg show no obvious difference. Significance. The proposed method can be used as a less complex way than conventional measurement of cfPWV to further assess arterial stiffness and predict cardiovascular risks or events.